2022
DOI: 10.3389/fonc.2022.1055376
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer analysis shows that ACO2 is a potential prognostic and immunotherapeutic biomarker for multiple cancer types including hepatocellular carcinoma

Abstract: BackgroundRecent evidence increasingly suggests key roles for the tricarboxylic acid cycle and fatty acid metabolism in tumor progression and metastasis. Aconitase 2 (ACO2) is a component of the tricarboxylic acid cycle and represents a key cellular metabolic hub that promotes de novo fatty acid biosynthesis. However, there have been few reports on the role of ACO2 in tumorigenesis and cancer progression.MethodsThrough the comprehensive use of datasets from The Cancer Genome Atlas, Genotype-Tissue Expression P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Here, we identified 5 metabolic hits associated with disease onset, progression, tumor aggressiveness, and survival in glioma patients (Figure 1). As mentioned earlier, two of the metabolic hits we identified, namely ACO2 and SOAT1, have already been established as biomarkers of disease progression in gliomas through their involvement in lipid metabolism (35,36). This also aligns with previous research showing that metabolic changes, such as aberrantly regulated glucose and lipid metabolism, play a pivotal role in disease aggressiveness in gliomas (18).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Here, we identified 5 metabolic hits associated with disease onset, progression, tumor aggressiveness, and survival in glioma patients (Figure 1). As mentioned earlier, two of the metabolic hits we identified, namely ACO2 and SOAT1, have already been established as biomarkers of disease progression in gliomas through their involvement in lipid metabolism (35,36). This also aligns with previous research showing that metabolic changes, such as aberrantly regulated glucose and lipid metabolism, play a pivotal role in disease aggressiveness in gliomas (18).…”
Section: Discussionsupporting
confidence: 88%
“…In order to validate our findings at the protein level, we also checked the protein expression of these metabolic hits in the CPTAC protein abundance database; we found that protein expression of these metabolic hits aligns well with RNA expression as ACO2 is down-regulated in gliomas compared to normal tissue whereas NAGLU, NT5DC2, PRIM2 and SOAT1 are up-regulated in gliomas compared to normal tissues (Figure 1F-J). Interestingly, two of these metabolic hits have already been established as biomarker of disease progression in gliomas through their involvement in lipid metabolism (35,36), thereby validating our analysis pipeline and findings. ACO2 is a key enzyme in tricarboxylic cycle (TCA) and tightly regulates the production of mitochondrial citrate that is precursor metabolite for de novo fatty acid biosynthesis and lipogenesis.…”
Section: Metabolism-targeted Expression Analysis Identifies Key Metab...supporting
confidence: 68%
See 1 more Smart Citation
“…Aconitase plays a role in regulating resistance to oxidative stress and cell death ( 31 ). ACO2 may be used as an immunotherapeutic and potential prognostic biomarker for several cancers, including hepatocellular carcinoma ( 32 ). ACO2 correlates with colorectal cancer cell survival ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of ACO2 in colorectal cancer promotes cell proliferation and colorectal cancer growth ( 235 ). However, compared with normal hepatocytes, ACO2 was overexpressed in HCC cells, promoting cell proliferation and migration by affecting molecular pathways involved in cellular energy metabolism, metabolite changes, and fatty acid metabolic pathway ( 233 ).…”
Section: Mitochondrial Disordersmentioning
confidence: 99%